ANALISIS BISNIS CABAI MERAH ON SEASON DAN OFF SEASON PADA UD. MITRA TANI DI KABUPATEN MAGELANG - Siti Syamsiar; Wulandari Dwi Etika Rini; Paramita Dewi Sulistyowati (Jurnal Dinamika Sosial Ekonomi, 2010)
Analyze Business Red Pepper On Season and Off Season in UD. Mitra Tani in Magelang Regency. The purpose of this reasearch is to analyze land productivity business red pepper on season and off season in UD. Mitra Tani; to analyze efissiensi business red pepper on season and off season in UD. Mitra Tani. The reasearch method used is case study methode. The kind of data used are primary data and secondary data. The source of the data taken from UD. Mitra Tani, relation institution with the reasearch and library reasearch. To analyse the efficiency of red pepper on season and off season in UD. Mitra Tani used trial and error analysed. Result of the reasearch show that land productivity business red pepper on season and off season in UD. Mitra Tani is 1.396,9 kg/ha and that land productivity business red pepper on season and off season in UD. Mitra Tani is 1.221,36 kg/ha. Result of the reasearch show that efficiency business red pepper on season and off season in UD. Mitra Tani is 0.92. Result of the reasearch show that efficiency business red pepper on season and off season in Mitra Tani is 1,36.Keyword : Business farm red pepper, on season, off season